Evaluation of anti-tuberculosis potentials of selected medicinal plants in Endau Rompin, Johor, Malaysia - Sanusi, Shuaibu Babaji (2018)
Tuberculosis (TB) remains an escalating health crisis globally which prompts new approaches to find more effective therapeutic strategies. Medicinal plants of Malaysia have a significant role to play in being able to provide new therapeutic remedies. The local people of Kampung Peta (Jakun tribe), Endau Rompin claimed that local preparations of some plants are used to treat symptoms of tuberculosis. There is a need to validate the claim by tradition healers scientifically. The aim of this research is to search for anti-TB from plants of Taman Negara Johor Endau-Rompin, exploiting the traditional medical practices of the Jakun people. Aqueous and organic extracts of these plant species were screened for their antimycobacterial activity using agar disk diffusion assay, Tetrazolium Microplate Assay and agar plate assay against Mycobacterium smegmatis. The effect of the extract on mycobacterial cell at the cellular level was investigated upon treatment with the crude extracts via time-kill analysis, leakage of compound absorbing at 280nm, and field emission-scanning electron microscopy (FE-SEM). The findings revealed that methanol extract of Nepenthes ampularia displayed the largest zone of inhibition (DIZ=18.67 ± 0.58 mm). Ethyl acetate extract of Musa gracilis and hexane extract of N. ampularia exhibited the lowest minimum inhibitory concentration (MIC=0.39 mg/mL). Hexane extract of N. ampularia showed the lowest minimum bactericidal concentration (MBC= 1.56 mg/mL). At 3-fold of MIC, hexane extract of N. ampularia, ethyl acetate extract of M. gracilis and ethyl acetate extract of N. ampularia killed the entire bacterial cell within 8 h of exposure by causing the cell lysis. The GC-MS analysis revealed the presence of phytoconstituents that might contribute to the antimycobacterial effect. The study scientifically justified the use of the selected medicinal plant species by Jakun people. Further studies on N. ampularia and M. gracilis could lead to the development of new anti-TB drugs.